Policy Implementation of Marine Protected Areas Program in Indonesia: a Case Study of The Marine Recreational Park of Gili Meno, Gili Ayer, and Gili Trawangan, West Nusa Tenggara, Indonesia - A. Boby Yefry Adi Rianto; Bambang Supriyono; M.R. Khairul Muluk (Jurnal Pembangunan dan Alam Lestari)
Abstract